Perancangan Website E-commerce Soemardjan Florist Menggunakan Framework Laravel - Anggara, Richardus Sapta; Pakereng, Magdalena A. Ineke (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Soemardjan Florist is one of the biggest florists in Salatiga, Central Java. Nearly 70% of Soemardjan Florist customers come from outside Salatiga City. Frequent found case is that customers come outside Salatiga but they sent the wreaths to weddings which is located in the Salatiga area. This proves that Soemardjan Florist has the potential to expand the market outside Salatiga city. In this research, the Soemardjan Florist website was developed to expand the Soemardjan Florist business. The website is built in PHP programming language using Laravel 5.5 framework. User test results indicate that Soemardjan Florist website can useful as a promotional media and online store as it should.